The complete mitochondrial genome of Claea dabryi (Teleostei, Nemachilinae, Claea). (4th May 2017) - Li, Qiang; Liu, Ya; Chen, Yeyu; Xiao, Yu; Du, Jun
Abstract: Claea dabryi is a small bottom-dwelling fish that is endemic to the upper stream of the Yangtze River. In this study, we successfully sequenced the first mitochondrial genome of C. dabryi . The mitogenome is 16 569 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and a control region (D-loop). Most of the genes are encoded on the heavy strand, except for eight tRNAs ( tRNA Gln, tRNA Ala, tRNA Asn, tRNA Cys, tRNA Tyr, tRNA Ser, tRNA Glu, and tRNA Pro ) and ND6 gene. In this paper, we utilized 12 protein-coding genes of C. dabryi and other 11 closely species to construct the species phylogenetic tree to verify the accuracy of C. dabryi .